USING A MONOTONE SEQUENCE OF FUNCTIONS TO DETERMINE THE SHORTEST ARC LENGTH OF CIRCLES CONNECTED ANY TWO POINTS ON SPHERE - Djafar, Muhammad Kabil; Safiuddin, La Ode; Laome, Lilis; Muhtar, Norma; Budiman, Herdi; Cahyono, Edi; Gubu, La.; Alfian, Alfian; Alamsyah, Indra; Kohalsum, Askar (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
This paper discusses about arc length of circles that connected any two points on a sphere. On a sphere, there are infinitely many circles that connect any two points. Using a monotone sequence of functions, we can show that the shortest arc length of circle that connect any two points on sphere is the circle with its center at the origin.